The interface between customary laws of succession in the traditional justice system and the formal justice system in - Mutema, Angela N. (UWC, 2020)
Doctor Legum - LLD === Traditional justice systems (TJS), which apply African customary law (ACL), play a significant role in the regulation of various cultural, social, and economic spheres of individual lives in society. It is estimated that 90% of African countries use TJS in dispute resolution. Succession matters form one of the areas in which TJS are applied. In Kenya, it is estimated that the majority of succession matters are addressed through TJS given that only 36% of cases are taken to the formal justice system (FJS) for determination. This indicates the presence of legal pluralism where formal law co-exists with African customary law. However, the application of customary succession laws and their enforcement by the FJS encounter impediments which curtail the integration of ACL within the FJS. Therefore, the purpose of this study is to determine the interface between African customary laws of succession in the TJS and the FJS. In order to achieve this objective the study applies the Historical School of Jurisprudence as its theoretical framework and applies document analysis as the research methodology. The major findings of the study indicated that though progressive recognition, application and enforcement of ACL in Kenya has been realised, there are several impediments to the integration and enforcement of customary succession decisions within the FJS. These include non-complimentary legal provisions, lack of in-depth knowledge on ACL by the FJS, and more importantly, lack of a policy guideline on the integration of ACL within the FJS. Based on these findings, this study finds it necessary to develop a guideline that will enhance the integration and enforcement of customary succession decisions by the FJS.